“The biggest thing you can rob is somebody's time”: Exploring how the carceral state bankrupts fathers through temporal debt - Henson, Abigail (Punishment & society, 2024)
Over the last several decades, research has demonstrated the adverse impact incarceration has on sustaining and strengthening familial bonds. Physical and communication barriers are often noted as lead sources of strain in relationships between incarcerated individuals and their loved ones. Studies have shown that the financial burden of prison can also have deleterious impacts on the family reintegration process upon release, particularly for minoritized populations. The current study adds to the discussion on collateral consequences of the carceral state by introducing temporal debt; a novel concept similar to financial debt in that it results from oppressive policies and builds over generations. Findings detail how the carceral state impacts fathers’ regard for temporal provision and enters Black men into a cycle of temporal poverty. The results encourage readers to consider novel means of addressing harm and violence to decrease the perpetuation of familial harm committed by the criminal legal system beyond reformist efforts that often aim to ease parenting from prison.